2009
DOI: 10.1074/jbc.c109.034058
|View full text |Cite
|
Sign up to set email alerts
|

SCHEMA Recombination of a Fungal Cellulase Uncovers a Single Mutation That Contributes Markedly to Stability

Abstract: A quantitative linear model accurately (R 2 ‫؍‬ 0.88) describes the thermostabilities of 54 characterized members of a family of fungal cellobiohydrolase class II (CBH II) cellulase chimeras made by SCHEMA recombination of three fungal enzymes, demonstrating that the contributions of SCHEMA sequence blocks to stability are predominantly additive. Thirty-one of 31 predicted thermostable CBH II chimeras have thermal inactivation temperatures higher than the most thermostable parent CBH II, from Humicola insolens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 14 publications
2
70
0
Order By: Relevance
“…Several routes exist for increasing cellulase performance, including rational and evolutionary methods to improve specific activity (8), screening for improved thermal tolerance (11,12), and the often overlooked strategy of increasing binding affinity to carbohydrates via CBM engineering (13)(14)(15)(16). In the lattermost case, several groups have shown that by increasing CBM binding affinity to cellulose via single point mutations or by swapping complete CBMs from other enzymes with higher binding affinity, cellulase enzyme activity can be improved (15,16).…”
mentioning
confidence: 99%
“…Several routes exist for increasing cellulase performance, including rational and evolutionary methods to improve specific activity (8), screening for improved thermal tolerance (11,12), and the often overlooked strategy of increasing binding affinity to carbohydrates via CBM engineering (13)(14)(15)(16). In the lattermost case, several groups have shown that by increasing CBM binding affinity to cellulose via single point mutations or by swapping complete CBMs from other enzymes with higher binding affinity, cellulase enzyme activity can be improved (15,16).…”
mentioning
confidence: 99%
“…This suggests that each sequence/structural block behaves differently in different contexts. For certain soluble protein properties (e.g., thermostability), it has been shown that block contributions are additive, that is, context independent, and that chimera stability can be predicted using linear regression (28,29,49,50). Our data suggest that ChR localization and photocurrent properties, however, require a more complex model to account for the nonlinear dependence of function on block sequence.…”
Section: Resultsmentioning
confidence: 75%
“…Interestingly, the recombinant enzyme displayed resistance to glucose inhibition in addition to thermotolerance. Others have reported on the expression of thermotolerant cellulases in yeast using a mutagenesis and recombination strategies rather than a discovery approach to further improve stability and activity of the recombinant enzymes [23][24][25].…”
Section: Recombinant Cellulase Expression In Saccharomyces Cerevisiaementioning
confidence: 99%